The Nodal Market Power Index (NMP Index) for Modelling and Visualising Market Power - Hesamzadeh, M.; Biggar, D.; Wolfs, Peter (IEEE Power & energy Society, 2010)
This paper deals with a systematic way for modelling and visualising market power in liberalised electricitymarkets. The paper first introduces a new index termed the “Nodal Market Power” index, the NMP index. The NMP index is calculated based on the concept of “social welfare” in economics and the game theory in applied mathematics. The oligopoly electricity market is modelled through a non-cooperative game and the solution concept of the Nash equilibrium. The solution concept of Nash equilibrium is reformulated as an optimisation problem. To tackle the multiple Nash equilibria problem, the worst Nash equilibrium in terms of the social cost to the society is selected. Then after, the NMP index is calculated for each node of power system. A colour contour map is used for visualising the market power using the NMP index.